Strategi Dakwah Pimpinan Cabang Muhammadiyah Medan Tembung Dalam Membangun Citra Positif Islam Di Era Post-Truth - Dalimunthe, Nazira Salsabila; Soiman, Soiman (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This study aims to analyze the da'wah strategy of PCM at Medan Tembung District in building a positive image in the post-truth era. This qualitative study uses employ observation, interviews, and documentation for data collection. The results of the study show that PCM Medan Tembung implements a da'wah strategy that is in line with the challenges of the post-truth era, including through the principle of talking less and working more, Maghrib recitation activities, utilizing social media with the @masjidtaqwamuh account as a medium for disseminating positive information, and providing social assistance in the form of zakat and rice to the surrounding community. These strategies reflect the form of da'wah bil hal and da'wah bil hikmah as recommended in QS. An-Nahl verse 125, which is to call to the path of Allah with wisdom and good lessons. This concludes that the alignment between da'wah strategies and contemporary challenges is the key in building public trust in the post-truth era.